Global prevalence of quackery practices: a scoping review of definitions, regulations, and allied healthcare - Veesar, Ghulam Yaseen; Ather Akhlaq; Siddiqi, Ahson Qavi (Journal of the Pakistan Medical Association, 2024)
Advancements in medical science and digital access made it easier for individuals to seek appropriate treatment. Despite living in the current information era, the practice of quackery has continued worldwide. The current scoping review was planned to explore different definitions and laws related to quackery, and the acceptance of allied healthcare services in traditional, cultural and legal contexts. The review examined a total of 3,327 published studies and 400 pieces of grey literature, including existing laws, regulatory authority websites, news articles and reports. A total of 56 studies and 21 excerpts were shortlisted for analysis. The definitions of quackery varied significantly across regions, but a general consensus is that unauthorised healthcare practices constitute quackery. Legal perspectives differed worldwide, with Europe, North America and Oceania discouraging allied healthcare services, such as homeopathy, naturopathy and traditional methods, considering them quackery. ---Continue